Corporate financing costs and ESG disclosure: evidence from Chinese A-share listed companies - Ren, Sixin; Mohd Isa, Salmi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The management of environmental, social, and governance (ESG) challenges by firms, which have an impact on their ability to create longterm value, is of increasing importance to investors. To inform stakeholders about their ESG performance and strategies, companies frequently disclose ESG data. Using data from China’s A-share listed companies from 2013 to 2022, this study used a fixed effect model to assess how ESG information disclosure effected corporate financing costs. The results showed that the company’s ESG disclosure, in particular equity funding, is related to the reduction in financing costs, and the 2018 update to the “Guidelines for Corporate Governance of Listed Companies” significantly contributed to this relationship. The study also examined the mechanism by which the publication of ESG information impacted financing costs and discovered that it decreases information asymmetry and enhanced stakeholder perception of the company. The study also demonstrated that businesses in high-profit, polluting industries had greater financing costs than those in low-pollution industries. This study emphasized the importance of incorporating ESG principles into current financial decision-making and sustainable corporate practices, as well as the value of doing so to boost social responsibility while decreasing spending.